Landscape, memory, and post-violence in Cambodia - Tyner, James A. 1966- (Rowman & Littlefield, 2017)
"Explores how the legacy of violence during the Khmer Rouge regime in Cambodia is memorialized. Engaging with war, violence and critical heritage studies, the book looks at the selective production of heritage diminishes opportunities for justice and reconciliation beyond the violence. It should be of particular interest to students and scholars interested in heritage studies, memory, trauma, genocide, dark tourism, and Cambodia".